BP-3 exposure at environmentally relevant concentrations induced male developmental reproductive toxicity via ER/CCL27/ROS pathway in mice - Hong-Mei Li; Yan-Rong Gao; Qing Chang; Xiu-Ying Pei; Jia-He Sun; Yu-Jia Lin; Ya-Nan Tian; Qiang-Wang; Bin Zhao; Heidi Qunhui Xie; Hui-Ming Ma; Hai-Ming Xu (Ecotoxicology and Environmental Safety)
BP-3 is the most widely used ultraviolet absorber, but its toxic effects and mechanisms far from being elucidated. This study evaluated the male developmental reproductive toxicities and mechanism of low-doses of BP-3. The results indicated that BP-3 (2.28 and 228 μg/L) led to a decrease in sperm quantity, quality and testosterone level, impaired blood-testis barrier (BTB) integrity and cytoskeleton, accompanied by aggravated oxidative stress in testes of mice on postnatal day 56 (PND 56). Notably, chemokine CCL27, a driver of oxidative stress, was significantly upregulated induced by BP-3. Similar disrupted effects were detected in testes of mice on PND14, which could be antagonized by ICI 182780 (estrogen receptor antagonist). Mechanistically, BP-3 directly interacted with ER, which boosted CCL27 expression, reactive oxygen species (ROS) accumulation, and BTB and cytoskeleton impairment. In vitro, si-CCL27 and/or ROS scavenger treatment significantly antagonized BP-3-induced oxidative stress and the decrease of BTB and cytoskeleton related genes in TM4 cells. These findings demonstrate that prolonged exposure to low-doses of BP-3 resulted in detrimental effects on testicular development through activation of the ER/CCL27/ROS axis. This study provides a novel perspective understanding the male reproductive toxicity risk caused by BPs exposure at low-doses.